The Wiley-Blackwell encyclopedia of eighteenth-century writers and writing, 1660-1789 / [electronic resource] - Baines, Paul, 1961-; Ferraro, Julian; Rogers, Pat, 1938- (Malden, MA : Wiley-Blackwell, 2011)
The Wiley-Blackwell Encyclopedia of Eighteenth-Century Writers and Writing 1660-1789 features coverage of the lives and works of almost 500 notable writers based in the British Isles from the return of the British monarchy in 1660 until the French Revolution of 1789.: Broad coverage of writers and texts presents a new picture of 18th-century British authorship; Takes advantage of newly expanded eighteenth-century canon to include significantly more women writers and labouring-class writers than have traditionally been studied; Draws on the latest scholarship to more accurately reflect the lite.
Introduction and further reading -- Timeline -- Entries.
Includes bibliographical references and index.
Print version record.
Keywords: 1700-1799; English literature -- 18th century -- Encyclopedias; English literature -- 18th century -- Bio-bibliography -- Dictionaries; Authors, English -- 18th century -- Biography -- Dictionaries; Literature; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Authors, English; English literature; Schriftsteller; Litteratur -- historia -- 1600-talet.; Litteratur -- historia -- 1700-talet.; Großbritannien; Electronic books; Bio-bibliography -- Dictionaries; Biography -- Dictionaries; Encyclopedias